2021
DOI: 10.1136/bjsports-2021-104060
|View full text |Cite
|
Sign up to set email alerts
|

Femoroacetabular impingement syndrome and labral injuries: grading the evidence on diagnosis and non-operative treatment—a statement paper commissioned by the Danish Society of Sports Physical Therapy (DSSF)

Abstract: This statement summarises and appraises the evidence on diagnostic tests and clinical information, and non-operative treatment of femoroacetabular impingement (FAI) syndrome and labral injuries. We included studies based on the highest available level of evidence as judged by study design. We evaluated the certainty of evidence using the Grading of Recommendations Assessment Development and Evaluation framework. We found 29 studies reporting 23 clinical tests and 14 different forms of clinical information, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Supporting this, each clinical entity seems to have distinct anatomical representations in patients with only one type of clinical entity (Serner et al, 2022). However, clear relationships between tissue injuries/pathology and longstanding groin pain classified into clinical entities using pain provocation tests are still lacking (Drew et al, 2014;Ishøi et al, 2021). Furthermore, the associations between longstanding groin pain and abnormal radiological findings lack robustness, temporal validity, and consistency (Branci et al, 2013Heerey et al, 2020;Massa et al, 2020;Paajanen et al, 2019;Robinson et al, 2015;Saito et al, 2021;Serner et al, 2021;Tsukada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, each clinical entity seems to have distinct anatomical representations in patients with only one type of clinical entity (Serner et al, 2022). However, clear relationships between tissue injuries/pathology and longstanding groin pain classified into clinical entities using pain provocation tests are still lacking (Drew et al, 2014;Ishøi et al, 2021). Furthermore, the associations between longstanding groin pain and abnormal radiological findings lack robustness, temporal validity, and consistency (Branci et al, 2013Heerey et al, 2020;Massa et al, 2020;Paajanen et al, 2019;Robinson et al, 2015;Saito et al, 2021;Serner et al, 2021;Tsukada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…18 A recent Danish Society of Sports Physical Therapy statement reported that physical therapy demonstrated a small to medium effect size as compared with passive modalities in patients with symptoms associated with FAIS and labral injuries; however, physical therapy was inferior to hip arthroscopy (although the quality of evidence for either was very low to moderate). 13 This was supported by Griffin et al, 10 who found that hip arthroscopy led to greater improvement at 12 months than nonoperative management in patients with FAIS. Nonetheless, a systematic review and meta-analysis revealed that despite the lack of high-quality randomized controlled trials (RCTs), physical therapist-led interventions (of 3 months) may improve pain and function in young and middle-aged adults with hip-related pain.…”
mentioning
confidence: 79%
“…2 The radiographic findings include cam, pincer or mixed morphology, and these morphological changes, especially cam, may lead to labral and cartilage lesions, and subsequently early hip osteoarthritis. [1][2][3][4][5][6][7][8] Furthermore, it is increasingly recognised that FAIS might account for previously undiagnosed hip pain in young adults. 5 9 Patients with FAIS usually present with hip pain, limiting activities of daily living, sports participation and hip-related quality of life (QoL).…”
Section: Introduction Background and Rationalementioning
confidence: 99%